Blockchain technology and sports : the impact of NFTs in the sports industry - Mendonça, André Guerreiro (2022)
Non-fungible tokens are scarce digital assets stored in a blockchain, that can be used to represent unique items related to the most various business sectors. The key value of this concept is the authenticity of each digital asset, since each token is tracible and the blockchain prevents the data from being replicated, offering a secure and transparent sense of ownership to its users. The results of this study point to the commercial potential implicit in the usage of this technology by professional football clubs, as well as a growing potential for the capitalization of this concept through different applications.